Surface roughness comparison of methacrylate and silorane-based composite resins after 40% hydrogen peroxide application - Sasmita, Rori; Adang, Rahmi Alma Farah; Hidayat, Opik Taofik (Padjadjaran Journal of Dentistry, 2012)
The change of the tooth colour could be restored with bleaching. The tooth bleaching will affects the surface roughness of the composite resins. Recently, the material basis for composite resins has developed, among others are methacrylate-based and silorane based composite resins. The objective of this study was to distinguish the surface roughness value of methacrylate-based composite resin and silorane based composite resins. This research was quasi-experimental. The sample used in this study were methacrylate and silorane based composite resins in discs form, with the size of 6 mm and the thickness of 3 mm, manufactured into 20 specimens and divided into 2 groups. The control group was immersed in the artificial saliva, and the treatment group was applied with 40% hydrogen peroxide. The result of the experiment analyzed using unpaired sample t-test showed significant differences in the average value of the surface roughness after the application of 40% hydrogen peroxide. The average value of methacrylate and silorane based composite resins were 2.744 Î¼m and 3.417 Î¼m, respectively. There was a difference in the surface roughness of methacrylate and silorane based composite resin compounds after the application of 40% hydrogen peroxide. The surface roughness value of the silorane-based composite resin was higher than the methacrylate-based.